Variable side-cut ski for a carved turn - Yoneyama, T. (Sports Engineering, 2018)
The relation between the ski side-cut radius and deflection during a turn has been investigated. Using a model wherein the ski slides along a turn of a constant radius with an edging angle, it was found that the side-cut radius increases and the ski-deflection radius decreases as the edging angle increases. Even if additional deflection is necessary in the front part of the ski to form the turn groove, the side-cut radius is still the same in the groove. Owing to the constant side-cut radius of existing skis in the turn groove with a large edging angle, the top wide part of the ski causes an increase in skiing resistance. To reduce the skiing resistance, a prototype variable side-cut ski was fabricated, and test skiing was performed. Athletes felt more stable in the turn with the variable side-cut ski and found it easier to increase speed.